Book Review of Art Curriculum and Instruction in Education - Mohammad Amini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the main functions of the educational system the  implementation of which at schools and educational centers of the country is confronted with various difficulties and misunderstandings is art education of students. Obviously, art education has positive and constructive effects for students, so it should not have a subordinate or marginal role in curriculum, and close attention should be paied to it in the educational system of the country. However, over the past few years, some scientific and research efforts have been made to introduce and recognize the status of art education and the need to pay close attention to it in the educational system of the country. Writing a book titled “Art Curriculum and Instruction in Education” is one of these scientific endeavors. In this article, the book has been reviewed and criticized.  The strengths and weaknesses of its content and form were also specified. In sum, in terms of the structure and type of organizing the contents, characteristics of writing, the design of the basic issues of art education, explanation of  its role and necessity, especially from its cognitive and non-cognitive results, as well as determining the role and place of the main elements of curriculum  in art education, this book has necessary strengths. On the other hand, in terms of the number and extent of its repetition and the similarity of its content with some other works of the authors, the vagueness of parts of the content, the use of translated articles and the lack of attention to the realities of art education in the Iranian educational system, this book has some deficiencies. Definitely, the elimination of these disadvantages will increase the effectiveness of this book.